Theoretical modelling of micro electro discharge machining for nonconductive ceramic materials - Abdus Sabur, Abu Naim Muhammad (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
In micro-electro discharge machining (micro-EDM) of nonconductive ceramics, material is removed mainly by spalling due to the dominance of alternating thermal load. Most of the existing theoretical micro-EDM models established for single spark erosion considering the melting and vaporization mechanisms are not applicable for nonconductive ceramics because of random spalling. In addition, it is difficult to create single spark on a nonconductive ceramic workpiece when the spark is initiated by the assisting electrode. In this study, theoretical models of material removal rate (MRR) and average surface roughness (Ra) as the function of capacitance and voltage are developed in resistance-capacitance (RC) pulse micro-EDM of nonconductive zirconium oxide (ZrO2) workpiece material. A correction factor (ε) is incorporated into the MRR model considering the spalling effect for multi-spark erosion. Charging and discharging duration are derived from the RC pulse time constant. It is shown that the charging and discharging duration depend on the capacitance and resistances of the circuit. The number of sparks per unit time is estimated from the single spark duration. The single spark erosion volume is derived from heat transfer equations. The Ra model is also adjusted by a correction factor (ψ). Both correction factors of ε and ψ are estimated as the function of process parameters capacitance and voltage based on experimental studies. The models show that both the capacitance and voltage are significant process parameters to the MRR and the Ra. It is shown that the increase of capacitance and voltage increases both the MRR and the Ra. Micro-EDM experiment showed that capacitance was the dominating parameter over voltage. In higher capacitances, the creation of a conductive carbonic layer on the machined surface was not stable. It was shown that effective machining was possible with the capacitance of 101 - 103 pF and gap voltage of 80 - 100 V or capacitance of 10 - 470 pF and gap voltage of 80 - 110 V. EDX analysis of EDMed surface produced by experiment using parameters within this range revealed the presence of higher carbon content contribute to produce conductive layer. The spark was found to be inconsistent using parameters beyond these ranges and consequently significant machining was not possible due to the insufficient amount of conductive layer forming on the workpiece. The experiment also showed that effective number of sparks per second were close to the predicted numbers when the conductive copper was machined. Higher percentage of ineffective pulses was also observed during the machining which reduced the effective energy and eventually the MRR. In the validation experiments, average deviations between the predicted and experimental values were found to be 10.50% and 7.04% for MRR and Ra respectively. Micro-channels were machined on nonconductive ZrO2 as an application of the models with micro-EDM process parameters selected based on the expected outputs. The resulted MRR and Ra of micro-channels were closed to the predicted values by the models with an average error of 8.86 % and 5.97 % respectively.